Social-psychological patterns in the mass consciousness of the post-Soviet society (second article) - Shamyakina, Tat’yana I. (Journal of the Belarusian State University. Sociology, 2019)
We consider the structure of human thinking, the effect of the unconscious factor in it, and in this connection new methods and methods of manipulating the mass consciousness are given on examples from the activity of the media of 2017. Attention is drawn to the importance for the creation of patterns of the introduction of various kinds of images, as well as to the suggestive impact of the language. Emphasis is placed on using manipulators to achieve philology in the analysis of various texts.